جنگ ِ آزادی 1857ء کے بعد ادب ِ سیرت ﷺمیں ہندوسیرت نگاروں کے رجحانات: Trends of Hindu Seerah Writers in Seerah Literature after War of Independence of 1857 - Dr. Noreen Butt (Al Manhal Research Journal, 2024)
It is the pride of the religion of Islam that where Allah has committed to the preservation of the Qur'an, also arranged to make the circumstances and life of the Prophet an authentic part of history so there is no room for any doubt or objection regarding the authenticity of Islam. Therefore, every aspect of the life of the prophet, is not only shining its own, but it is brightening the whole humanity. Regular compilations in the form of biographies were embellished and until today, the biographies of the Prophet are being presented with different aspects and approaches. Along with the services of Muslim historians and seerah writers, Hindu writers also have been making the biography of the Prophet their subject. Regardless of the fact that there are both appreciating and critical styles of writing in it, they worked in different methods and approches in both these trends. There are certain reasons and for adopting each of the two trends that are important for a researcher to be aware of these motives.in this article trends of hindu seerah literature and their methodology and purposes behind their writings have been discussed.